Efeito de um meio condicionado por células do Cumulus oophorus de bovinos na maturação e no potencial de desenvolvimento embrionário in vitro de oócitos desnudos - Isabela Maria Alves de Avila (2017)
One of the challenges of reproductive biology and medicine is to understand the nature of the molecular and cellular processes that control oocyte developmental competence. This competence, acquired through maturation, a complex process that comprises nuclear and cytoplasmic maturation, involves a deep interaction between the oocyte and Cumulus oophorus cells. Cumulus oophorus cells are key for paracrine and endocrine signaling and for oocyte maturation; however, in many applications, removal of these cells, or oocyte denudation, is required before maturation begins or prior to in vitro fertilization. Because denudation reduces developmental competence, an efficient in vitro maturation system for denuded oocytes is needed, as no system has been well established in mammalians. Different systems use co-cultures of homologous and heterologous cells or media conditioned by these cells, to take advantage of factors secreted by them and optimize results in in vitro production. The present study evaluates the effect of a medium conditioned by a culture of bovine Cumulus-oophorus cells in the in vitro maturation of bovine denuded oocytes and their embryonic development potential. The experiment was carried out in the Laboratory of in vitro Production of Embryos at the School of Veterinary Medicine, Federal University of Minas Gerais, Brazil. The oocytes were aspirated from follicles between 2 and 8 mm in diameter from slaughterhouse ovaries. Grade I and II oocytes, half of which had been denuded by successive pipetting prior to maturation, were matured in control medium and in the conditioned media previously obtained from the culture of Cumulus oophorus cells. 2927 oocytes were matured, of which 894 were used for evaluation of maturation and 2033 for evaluation of embryonic development. The evaluation of in vitro oocyte maturation was performed based on nuclear maturation, cytoplasmic maturation (mitochondrial distribution), enzymatic dissolution of zona pellucida with chymotrypsin 1% and pronase 0.5% and ultrastructure by transmission electron microscopy. The evaluation of embryonic development potential was based on embryo cleavage and blastocyst rates. There were no significant differences in nuclear maturation of oocytes in control medium and conditioned medium, as well as no differences between nuclear maturation of CCOs and denuded oocytes. Cytoplasmic maturation in conditioned medium was not significantly different from that in control medium. Denuded oocytes presented a predominantly heterogeneous-peripheral mitochondrial distribution pattern, whereas CCOs had a predominant heterogeneous-perinuclear pattern. Denuded oocytes matured in the conditioned medium showed a significant reduction of the dissolution time of the zona pellucida in enzymatic dissolution assay with chymotrypsin 1%, but there were inconsistencies between the results obtained in the assays with the two enzymes. There were no significant differences between cleavage and blastocysts rates between oocytes matured in control medium and conditioned medium. In conclusion, under these experimental conditions, the conditioned medium from bovine Cumulus oophorus cells did not prove to be superior to the control medium in relation to the in vitro oocyte maturation of the denuded oocytes nor with respect to its embryonic development and, therefore, its incorporation into in vitro embryo production routines is not recommended. Further studies are still needed to better understand the events related to the acquisition of oocyte competence and to develop more efficient in vitro maturation media for denuded oocytes.